El SIG y el patrimonio arqueológico en los valles del Turón y Guadalteba (Guadalhorce Medio). Su aplicación en la investigación histórica, paisaje y desarrollo turístico territorial - Fco. Javier Medianero Soto (Virtual Archaeology Review, 2010)
The valleys of Guadalteba and Turón are located in the middle basin Guadalhorce river in its western slope. The implementation of the Geographic Information Systems since the year 2000 enables the start of the research throughout the region of Guadalteba and in particular to areas such as Park Guadalteba. In this communication will an overview of the research generated in this framework territorial and in its application for the development of heritage resources that they generate proposals interpretative and innovation tourism.